2020
DOI: 10.1093/geronb/gbaa105
|View full text |Cite
|
Sign up to set email alerts
|

More Vulnerable? The Life Story Approach Highlights Older People’s Potential for Strength During the Pandemic

Abstract: OBJECTIVES Older adults have repeatedly been referred to as more physically vulnerable during the COVID -19 pandemic. The pandemic, however, is not only about becoming physically ill. It has many psychosocial aspects: people are exposed to myriad life challenges. The life story approach does not ignore physical status but also emphasizes psychosocial strengths. It highlights that older people are likely to have developed resilience through experiencing life challenges and living across histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 26 publications
(33 reference statements)
6
63
0
Order By: Relevance
“…These results have confirmed that older adults have social and psychological resources that allow them to face adversity. Older people have overcome past stressful experiences that could be encouraging them to overcome the confinement problems [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…These results have confirmed that older adults have social and psychological resources that allow them to face adversity. Older people have overcome past stressful experiences that could be encouraging them to overcome the confinement problems [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults, especially those with comorbid health conditions, are at elevated risk of COVID-19 morbidity and mortality compared to younger population groups ( 1 – 3 ). Beyond physical illness, the pandemic exposes older people to myriad life challenges including disrupted plans, frustration and boredom, separation from family and friends, irregular access to supplies (e.g., food, medication), and financial strain ( 4 , 5 ). Older adults may also be at heightened risk of pandemic-related personal losses such as bereavement of a family member or friend, job loss or reduced income if not retired, and long-term exclusion from participation in social and public activities ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the immense burden of COVID-19 on aging populations, it is essential to understand effective ways of coping with living through the pandemic. This paper contributes to an emerging counternarrative in response to ageist portrayals of older adults in popular discourse as vulnerable, frail, and disposable in the context of the COVID-19 pandemic [see also ( 4 , 9 )]. We shift from this negative perspective to focus on the psychosocial strengths and resiliencies of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, half of these studies utilize life span samples that allow for evaluating how older age predicts better or worse functioning ( Barber & Kim, 2020 ; Bruine de Bruin, 2020 ; Klaiber et al, 2020 ; Losada-Balter et al, 2020 ; Pearman et al, 2020 ). Moreover, two papers offer valuable perspectives on why being older may strengthen the ability to deal with adversity ( Lind et al, 2020 ) and the importance of using behavioral research to reduce ageism and promote intergenerational solidarity ( Ayalon et al, 2020 ).…”
mentioning
confidence: 99%
“… Klaiber and colleagues (2020) found that, in the early weeks of the pandemic, older adults did not differ from younger adults in their exposure to COVID-19 stressors, but did report better emotional well-being and less reactivity to stressors. As highlighted in the article by Lind and colleagues (2020) , older age may proffer psychosocial strengths for dealing with adversity that have been acquired through experiencing life challenges and living through historical periods of population-wide stressors and considerable societal change.…”
mentioning
confidence: 99%